A probabilistic relational database model and algebra - Nguyen, Hoa (Journal of Computer Science and Cybernetics, 2015)
This paper introduces a probabilistic relational database model, called PRDB, for representing and querying uncertain information of objects in practice. To develop the PRDB model, first, we represent the relational attribute value as a pair of probabilistic distributions on a set for modeling the possibility that the attribute can take one of the values of the set with a probability belonging to the interval which is inferred from the pair of probabilistic distributions. Next, on the basis representing such attribute values, we formally define the notions as the schema, relation, probabilistic functional dependency and probabilistic relational algebraic operations for PRDB. In addition, a set of the properties of the probabilistic relational algebraic operations in PRDB also are formulated and proven.